1989
DOI: 10.1136/bmj.299.6690.25
|View full text |Cite
|
Sign up to set email alerts
|

Early amniocentesis: a cytogenetic evaluation.

Abstract: We investigated the use of amniocentesis performed at eight to 14 weeks' gestation as a possible alternative to chorionic villus sampling. Patients, methods, and results Samples of amniotic fluid were taken from 40 gestation, and the mean time to the cells being harvested was 12 6 days. In contrast only 17 (68%) of the 25 samples taken at eight to 11 weeks yielded a result. One sample taken at 13 weeks' gestation yielded a female karyotype, whereas the fetal parts revealed a male karyotype; the sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…Since 1987, several uncontrolled series of early amniocentesis have been published (Miller et al, 1987;Godmilow et al, 1988;Cuoco et al, 1989;Evans et al, 1988Evans et al, , 1989Lituania et al, 1989;Richkind and Aleck, 1989;Rooney et al, 1989;Stripparo et al, 1989;Blache et al, 1990;Elejalde et al, 1990;Klapp et al, 1990;Lindner et al, 1990;Nevin et al, 1990;Penso et al, 1990;Stripparo et al, 1990;Thayer et al, 1990;Grujic et al, 1991;Hackett et al, 1991;Rebello et al, 1991;Assel et al, 1992;Bombard and Rigdon, 1992;Djalali et al, 1992;Hanson et al, 1992;Henry and Miller, 1992;Jorgensen et al, 1992;Gabriel et al, 1993;Huter et al, 1993;Kerber and Held, 1993;Eiben et al, 1994). When combined, these studies relate to results of EA in well over 10 000 women.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1987, several uncontrolled series of early amniocentesis have been published (Miller et al, 1987;Godmilow et al, 1988;Cuoco et al, 1989;Evans et al, 1988Evans et al, , 1989Lituania et al, 1989;Richkind and Aleck, 1989;Rooney et al, 1989;Stripparo et al, 1989;Blache et al, 1990;Elejalde et al, 1990;Klapp et al, 1990;Lindner et al, 1990;Nevin et al, 1990;Penso et al, 1990;Stripparo et al, 1990;Thayer et al, 1990;Grujic et al, 1991;Hackett et al, 1991;Rebello et al, 1991;Assel et al, 1992;Bombard and Rigdon, 1992;Djalali et al, 1992;Hanson et al, 1992;Henry and Miller, 1992;Jorgensen et al, 1992;Gabriel et al, 1993;Huter et al, 1993;Kerber and Held, 1993;Eiben et al, 1994). When combined, these studies relate to results of EA in well over 10 000 women.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of different studies of early amniocentesis has so far not revealed major differences in spontaneous fetal losses when compared with later gestations (Sundberg et al, 1995b). But culture failure rates are increased in the early weeks (Elajalde et al, 1990;Byrne et al, 1991;Thayer et al, 1990;Rooney et al, 1989;Nicolaides et al, 1996), which makes this approach less acceptable as a follow-up procedure.…”
Section: Discussionmentioning
confidence: 94%
“…However, several studies have reported higher culture failure rates when sampling amniotic fluid prior to week 14, which makes early amniocentesis with the conventional technique a less attractive approach as a follow-up procedure (Elejalde et al, 1990;Byrne et al, 1991;Thayer et al, 1990;Rooney et al, 1989). This is probably due to a lower cell concentration in the amniotic fluid during these earlier weeks (Elejalde et al, 1990).…”
Section: Introductionmentioning
confidence: 93%
“…Most authors agree that with amniocentesis from the 13th week onwards, enough material can be obtained, and it is a safe procedure and gives reasonably good results (Rebello et aI., 1991;Djalali et al, 1992). It is a clear alternative to CVS as a prenatal diagnosis procedure, but it is still a controversial issue with respect to previous gestations (Rebello et al, 1991;Rooney et al, 1989;Jorgensen et al, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…For 10-12 weeks it has been estimated in 8-21 days Eiben et al, 1994;Jorgensen et al, 1992;Hanson et al, 1992;Kerber and Held, 1993;Rebello et al, 1991;Mediano et al, 1992;Rooney et al, 1989).…”
Section: Discussionmentioning
confidence: 99%